Construction of the image of healthy living in a digital germ campaign: Kritis Analysis Jean Baudrillard - Muhammad Ilyas; Samsu A. Kamaruddin; Arlin Adam (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: The increasing use of social media by the Indonesian government as a platform for health promotion has led to the construction of visually appealing and idealized representations of healthy living. In the context of the Healthy Living Community Movement (GERMAS), these representations often emphasise symbolic aesthetics over everyday realities. This study aims to critically analyze how the digital GERMAS campaign constructs the image of healthy living through Jean Baudrillard’s theory of simulation and simulacra. Methods: This research employed a qualitative case study design conducted from August to October 2025, focusing on digital content disseminated through the official platforms of the Ministry of Health, including Instagram, YouTube, and the website kemkes.go.id. Data were collected through digital documentation, online observation, and in-depth interviews with ten informants from risk-vulnerable groups, comprising six adolescents and four homemakers. Thematic analysis was employed to identify symbolic patterns and narratives, which were then interpreted through the lens of Baudrillard’s conceptual frameworks. Results: Findings indicate that the GERMAS digital campaign constructs healthy living as a modern, visually attractive lifestyle that is often disconnected from the lived realities of the target audience. Adolescents perceived the content as aesthetically pleasing yet overly idealized, while homemakers viewed it as informative but challenging to implement due to economic and contextual barriers. Both groups highlighted that the campaign’s imagery often functions as a performative symbol rather than a reflection of authentic health practices. Conclusion: The study concludes that the digital campaign reinforces hyperreality, where symbolic representations of health are consumed more actively than the practices themselves. To achieve a meaningful behavioral impact, digital health communication must adopt more contextual and participatory approaches that resonate with everyday socio-economic conditions.